Factors associated with low bone mineral density in postmenopausal women with rheumatoid arthritis - Zahid, Pir Muhammad; Saba Samreen; Zafar Ayub Khan; Babur Salim; Syed Nazir Ahmed; Haris Gul (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the factors related to low bone density in postmenopausal women with rheumatoid arthritis. Method: The prospective cross-sectional study was conducted at the Rheumatology Department of Fauji Foundation Hospital, Rawalpindi, Pakistan, from June 1 to November 30, 2020, and comprised postmenopausal women with rheumatoid arthritis. On the basis of dual-energy X-ray absorptiometry scan of total hip, femoral neck, and lumbar spine, the subjects were categorised into osteoporosis, osteopenia and normal bone density groups. The risk factors were compared across these subgroups. Data was analysed using SPSS 21. Results: Of the 114 women, 74(64.9%) had osteoporosis, 31(27.2%) had osteopenia and 9(7.9%) had normal bone mineral density. Those with osteoporosis were older (p<0.05), had low body mass index (p<0.002) and had a longer duration since menopause (p<0.004) compared to the other groups. Age and body mass index were significant factors associated with the condition (p<0.05). Conclusion: Older age, lesser body mass index and time since menopause were the factors significantly associated with osteoporosis. Key Words: Rheumatoid arthritis, DXA, Bone mineral density.